Under the paper moon - Steinberg, Shaina (Kensington Publishing Corp., 2024)
Five years after working for the Office of Strategic Services with Nick, whom she gets close to until the World War II' end brings with it an act of deep betrayal, former spy Evelyn, now working as a PI, finds herself back in Nick's orbit when her latest case brings the war to her doorstep.